Preoperative Radiotherapy in Myxoid Liposarcoma - Fenny Tjuatja; H M Djakaria (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2020)
Myxoid liposarcoma are responsive to radiotherapy, particularly preoperative radiotherapy. The outcome of the preoperative radiation is a decreasing tumor size and major necrotizing area. With a good local control, organ functions can survive without any amputation. Preoperative radiotherapy can be given with or without chemotherapy. Conventional fractionation such as 25 x 2 Gy or hypofractionation 5 x 5 Gy could be an effective way to treat preoperative myxoid liposarcoma.